2001
DOI: 10.1073/pnas.98.4.1353
|View full text |Cite
|
Sign up to set email alerts
|

The origins of stability of spontaneous vesicles

Abstract: Equilibrium unilamellar vesicles are stabilized by one of two distinct mechanisms depending on the value of the bending constant. Helfrich undulations ensure that the interbilayer potential is always repulsive when the bending constant, K, is of order k BT. When K Ͼ Ͼ k BT, unilamellar vesicles are stabilized by the spontaneous curvature that picks out a particular vesicle radius; other radii are disfavored energetically. We present measurements of the bilayer elastic constant and the spontaneous curvature, R … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
353
1
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 281 publications
(375 citation statements)
references
References 38 publications
20
353
1
1
Order By: Relevance
“…Above the chain-melting temperature, with or without excess salt, diluted unilamellar vesicles are the most stable state, and in-plane mixing of the anionic and cationic components is ensured (12)(13)(14). In this molten state, rigidity of the bilayer is low (Ϸ1-10 k B T); and, thus, small unilamellar vesicles Ϸ50 nm in diameter can be formed without too much bending energy (15). Stability of micelles (at low temperature, when chains are crystallized) was discussed a long time ago by Fromherz (16).…”
Section: Model Mixed Molecular System Investigatedmentioning
confidence: 99%
“…Above the chain-melting temperature, with or without excess salt, diluted unilamellar vesicles are the most stable state, and in-plane mixing of the anionic and cationic components is ensured (12)(13)(14). In this molten state, rigidity of the bilayer is low (Ϸ1-10 k B T); and, thus, small unilamellar vesicles Ϸ50 nm in diameter can be formed without too much bending energy (15). Stability of micelles (at low temperature, when chains are crystallized) was discussed a long time ago by Fromherz (16).…”
Section: Model Mixed Molecular System Investigatedmentioning
confidence: 99%
“…41 In this case, the salt induces strong attractive interactions and the deformation stems directly from the vesicle clustering, i.e., close vesicle-vesicle interactions. 41 This type of mechanism where the role of salt could be replaced with the polycation does not take place here, since indiVidual faceted vesicles are observed in various samples at different temperatures above T m .…”
Section: Mechanisms For Polymer-induced Changes In Vesiclementioning
confidence: 99%
“…It has been shown previously that vesicles formed by catanionic surfactant mixtures of unequal chain length are typically polydisperse. 63 In a study by Coldren et al, 51 it has been shown that the stiffer (higher bending constant, K) the bilayer the less polydisperse the vesicle sample; these authors determined the sum of the Helfrich bilayer elastic parameters and the spontaneous curvature radius from the size distribution obtained from the cryo-TEM images for three different systems. Relating their results to ours, we can infer that the vesicle system composed of ALA and SOS probably has higher bilayer stiffness than that composed of ALA and SCS, resulting in a less polydisperse size distribution as can be seen in Figure 5b.…”
Section: Discussionmentioning
confidence: 99%